Assessing the Effectiveness of Green Business Practices on Nigerian Economic Sustainability: A Study of Dawaki Groups, Kano, Nigeria - Nduji Romanus; Marcus Garvey Orji; Oriaku Chris (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
The objective of this study is to assess the effectiveness of green business practices on Nigerian Economic Sustainability, with particular emphasis on Dawaki Groups, Kano, Nigeria. The study sought to achieve these sub objectives: determine the extent to which green product development affects the economic responsibility of Dawaki Groups, establish the extent to which waste reduction has an effect on the environmental responsibility of Dawaki Groups and identify the extent to which corporate partnership has influenced the social responsibility of Dawaki Groups. The population was 952 and a sample size of 281 was determined using Taro Yamani. Data were collected via online questionnaire. Linear Regression analyses were used to test the hypotheses. The findings revealed that green product development has a significant effect on the environmental responsibility of Dawaki Groups, Kano (sig =0.000 < 0.05, R2= 0.493 and t-statistic= 15.971), Waste reduction has significant effect on the environmental responsibility of Dawaki Groups, (sig =0.000 < 0.05, R2= 0.027 and t-statistic=2.707) and also Corporate partnership has a significant influence on social responsibility of Dawaki Groups,(sig =0.000 < 0.05, R2= 0.260 and t-statistic=9.582). The study concluded that the implementation of green business practices, principles and processes will lead to very positive outcomes that will be visibly manifested in the organization and the environment. The study therefore recommended that green business practice is the most potent alternative for dealing with environmental challenges as well as dealing with all performance problems of business firms.